2017
DOI: 10.1039/c7tc04084a
|View full text |Cite
|
Sign up to set email alerts
|

ITO-free, inkjet-printed transparent organic light-emitting diodes with a single inkjet-printed Al:ZnO:PEI interlayer for sensing applications

Abstract: ITO-free, vacuum-free, inkjet-printed transparent yellow OLEDs with a one-step inkjet-printed Al:ZnO:PEI interlayer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 37 publications
1
15
1
Order By: Relevance
“…Facing the shortage reserves of Indium, ZnO based TCOs draw people's attention because of their abundant reserves . In AZO or GZO, the substitution of Al 3+ or Ga 3+ for Zn 2+ provides an excess of electrons, forming n‐type semiconductors . By adjusting dopant concentration, one can get various distributions of refractive index and even gradient‐index in AZO/ZnO or GZO/ZnO mixtures.…”
Section: Methodsmentioning
confidence: 99%
“…Facing the shortage reserves of Indium, ZnO based TCOs draw people's attention because of their abundant reserves . In AZO or GZO, the substitution of Al 3+ or Ga 3+ for Zn 2+ provides an excess of electrons, forming n‐type semiconductors . By adjusting dopant concentration, one can get various distributions of refractive index and even gradient‐index in AZO/ZnO or GZO/ZnO mixtures.…”
Section: Methodsmentioning
confidence: 99%
“…Several other types of transparent electrodes have been investigated, including high conductivity polymers such as PEDOT:PSS, graphene‐based and other novel material electrodes, carbon nanotubes, Ag and Cu nanowires, Cu mesh, and a variety of thermally evaporated metal grids . Transparent metal oxides, used together with a metal (grid) contact, can also be evaporated or sputtered, while some metal oxides such as ZnO, Al‐doped ZnO, and WO 3 are routinely being deposited by solution‐processing, including inkjet‐printing …”
Section: The Printed Transparent Conductive Electrode In Organic Elecmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] But only a few studies reported all solution-processed OLEDs compared to OPVs. [20][21][22][23][24][25] The choice of the materials is the first step to address a lowcost R2R fabrication process. The widely used indium tin oxide (ITO) electrode represents almost half of the cost of an OLED device or an OPV device.…”
Section: Introductionmentioning
confidence: 99%